Re-imaging and re-imagining approaches to organizational change - Oswick, Cliff (Henry Stewart Talks, 2010)
Metaphors and change, Change as a three stage process, Analogical perspectives on change diagnosis, Dominant metaphors of organizational change, The health metaphor, The journey metaphor, The change equation, Comparing and contrasting processes, Summary of meta-framings of change, Inferences for managing change